2004
DOI: 10.1182/blood-2003-05-1737
|View full text |Cite
|
Sign up to set email alerts
|

MEK1,2 response element mediates angiotensin II—stimulated plasminogen activator inhibitor-1 promoter activation

Abstract: IntroductionPlasminogen activator inhibitor-1 (PAI-1) is the major regulator of both tissue and urokinase plasminogen activators. 1,2 Inhibition of plasminogen activation by PAI-1 reduces the generation of plasmin and thereby impairs fibrinolysis. In addition, PAI-1 has also been suggested to reduce plasmin-mediated activation of matrix metalloproteases 3 and compete with cellular ␣v␤3 integrin matrix interactions, which contribute to cellular migration. 4 Overexpression of PAI-1 in transgenic mice or by adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…The delayed stable induction of OPN and PAI-1 transcript by ANG II also agrees with previous findings that prolonged ERK leads to their induction (8,15). Persistent upregulation of junB in malignant hypertension may thus indicate a defect in the regulation of junB that contributes to remodeling and involves OPN and PAI-1 expression.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The delayed stable induction of OPN and PAI-1 transcript by ANG II also agrees with previous findings that prolonged ERK leads to their induction (8,15). Persistent upregulation of junB in malignant hypertension may thus indicate a defect in the regulation of junB that contributes to remodeling and involves OPN and PAI-1 expression.…”
Section: Discussionsupporting
confidence: 78%
“…injury in Dahl S rats (18). In cultured VSMCs, ERK phosphorylation induced by mechanical injury leads to the overexpression of OPN protein, and ANG II induces PAI-1 expression in a ERK-dependent manner (8,31). Furthermore, OPN and PAI-1 were identified in a matricellular gene cluster as highly ANG II responsive (7).…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, knockdown of endogenous thymosin ␤4 prevented Ang II-induced PAI-1 expression. Previous data have shown that Ang induces PAI-1 upregulation via c-Fos/c-Jun binding to Sp1 and activated protein-1 sequences in the PAI-1 promoter (35). Of note, thymosin ␤4 enhances c-Fos/c-Jun DNA-binding activity to the activated protein 1 element (26).…”
Section: Discussionmentioning
confidence: 91%
“…45 Additionally, the participation of the ERK pathway in the A23187-dependent PAI-1 induction in this study is in line with a recent report on the Ang-II-mediated PAI-1 expression in VSMCs. 61 Although the latter study did not investigate the direct involvement of Ca 2ϩ in Ang-II-dependent PAI-1 expression, it was shown that the Ang-II-dependent PAI-1 promoter activation requires the coactivation of specific ␤-1 glycoprotein (SP-1) and AP-1. 61 Thus, it appears that, depending on the stimulus and the cell type downstream from ERK, different transcription factors may activate PAI-1 expression.…”
Section: Calcium-dependent Pai-1 Gene Expression Under Physiologic Anmentioning
confidence: 99%